(untitled) (Research, Society and Development, 2021)
Cigarette smoke compromises the salivary glands, altering saliva. Cotinine is the most effective biomarker to assess tobacco consumption, and passive smokers are characterized by serum cotinine levels above 2.1 ng/mL. This study aimed to evaluate the effect of exposure to cigarette smoke on rats submandibular glands. The morphology, the proliferative cells of intercalated ducts (immunohistochemistry for KI-67) and its correlation with serum cotinine levels were analyzed. Wistar rats were grouped: control (C); inhalation of smoke for 30 days (T1) and 60 days (T2). Data were analyzed with the Levene variance homogeneity test, Spearman’s test, ANOVA and Tukey’s post-test, with significance p<0.05. Morphology showed a preserved parenchyma in C, and altered secretory cells in T1 and T2. There was a significant reduction in the number of proliferative cells [ANOVA, F = 4.726; d.f. = 2, 26; p<0.05]: C vsT1 (p<0.05) and C vs T2 (p<0.05). T1 and T2 serum cotinine levels were significantly higher (p<0.05) than C. There was a significant negative correlation [ρ = -0.418, n=27, p<0.05] between serum cotinine levels and the rate of cellular proliferation. These results suggest that of tobacco smoke inhalation has a decreased of the cellular proliferation rate and altered morphology in submandibular glands de ratos Wistar.